A comprehensive approach na gestão de crises internacioanis - Fiel, Carolina Monteiro (2017)
This study focus on the analysis of the Comprehensive Approach, in NATO and the UN, in crisis management, and supports the argumente that the two organizations have divergente approaches. Starting from the primary purpose, the concolidation of the planning and the modus operandi, the CA was adopted and refreshed by the International Organizations, as a nem form of adaptation to the new expansion of tasks, time and actors, and the interaction between them. In this sense, the argumente was built by studying the institutional evolution of the CA, the actors, the crisis management, the capacities, the internal and external cooperation and the case of studies of Afghanistan and Liberia, in NATO and UN, respectively. In the investigation, it is perceived the intention of UN of contributing to a longlasting peace, by their multiple organizations, and the intention of NATO to contibute as a part of the international community to the CA. Even though they have their institutional diferences, the simultaneous pursuit of Strategy and the use of Whole-of-Government Approach as an operational method, makes them operationally similar, converging into a possible cooperation on the long term, and a future joint commitment on crisis management.